Framework for Rural Development through an Modern Agribusiness System Based on Local Commodities: A Pilot Study in Suci Village, Jember Regency, East Java, Indonesia - Linda Ekadewi Widyatami; Luluk Cahyo Wiyono; Moh. Munih Dian Widianta; Datik Lestari; Akbar Maulana Firmansyah (Journal of Business Management, 2025)
The development of agribusiness based on village level flagship commodities cannot be carried out in a partial or fragmented manner. It requires an integrated agribusiness system approach that encompasses the entire value chain from upstream to downstream. The objective of this study is to identify the potential of village flagship commodities within an integrated agribusiness system and to develop an Agribusiness Modernization System (AMS) through a case study conducted in Suci Village, Panti Subdistrict, Jember Regency, East Java. Agribusiness modernization has been shown to facilitate the introduction of appropriate technologies, enhance value-chain efficiency for agricultural products, and strengthen the capacities of farmers and local enterprises. Flagship commodities can be determined not merely by historical quantitative advantages but by competitive potential validated through four empirical domains: (1) biophysical contextuality verification, (2) sensory quality validation, (3) market valuation assessment, and (4) institutional readiness analysis. This study demonstrates that integrating the pillars of socio-economic governance with biophysical potential yields a comprehensive approach to rural development. The Place-Based Commodity Selection Framework provides a definitive answer to the fundamental question of commodity selection by moving beyond descriptive–historical methods toward a prescriptive–strategic paradigm. The four-domain analysis convincingly identifies coffee as the flagship commodity of Suci Village, with validation supported by convergent evidence on biophysical suitability, sensory quality potential, significant economic value opportunities, and institutional preparedness. Thus, this study makes a practical contribution to the development of sustainable and competitive rural agribusiness.